2019
DOI: 10.1515/humo-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Psyhical effort, energy expediture, and motivation in structured and unstructured active video games: a randomized controlled trial

Abstract: Purpose. The goals of the study were: a) to compare the way that two types of active video games (AVG) influenced physical effort and motivation in young adults; b) to compare direct and indirect instruments and use an indirect instrument (heart rate analysis) as a practical tool to verify physical effort in AVGs. Methods. Initially, 16 healthy but physically inactive young adult males with no AVGs experience took part in the randomized control trial. After the baseline assessments of blood pressure (BP), hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 36 publications
(37 reference statements)
0
33
1
Order By: Relevance
“…Previous studies have reported that a single AVG session induces a significant increase in HR, SBP, DBP, and hence in DP [1,2,4,5,23]. However, the PEH phenomenon in relation to AVG remains unclear.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have reported that a single AVG session induces a significant increase in HR, SBP, DBP, and hence in DP [1,2,4,5,23]. However, the PEH phenomenon in relation to AVG remains unclear.…”
Section: Resultsmentioning
confidence: 95%
“…In the present study, small effects on blood pressure were observed after a 4-week AVG intervention, whereas there was resting bradycardia as a chronic effect of the intervention. Even if HR is a commonly measured clinic variable in response to vascular effects, most studies record it at rest and during AVG sessions as a tool to determine the intensity of the games [1,2,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AVG interventions need to be structured and supervised to produce positive effects on energy expenditure. No effects were found on physical activity or energy expenditure in home-based and/or unstructured AVG interventions [ 34 , 35 ]. In the present study, not only was a planned and structured intervention carried out, but it was combined with traditional physical exercise with the aim of increasing energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…AVG interventions need to be structured and supervised. because no effects were found on physical activity or energy expenditure in home-based and/or unstructured AVG interventions [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%